The Relationship between Sevoflurane Volatile and Time to Recover from Consciousness in Patients After General Anesthesia - Rahmadiya Hadi Putri; Asmat Burhan; Feti Kumala Dewi (Global Indonesia Health Care (GOICARE), 2025)
Prolonged recovery time is one of the undesirable complications in anesthesia procedures so it is necessary to prevent delayed recovery of consciousness from occurring in patients. Volatile sevoflurane is considered as one of the main options because of its safety profile and the speed of recovery of post-anesthesia patients. The purpose of the study was to determine the relationship between volatile sevoflurane and time to recover consciousness in patients after general anesthesia at Kardinah Hospital, Tegal City. This research method is descriptive correlation with cross sectional design. The sampling of this study was consecutive sampling consisting of 128 people. Data collection techniques intra and post anesthesia with general anesthesia using a questionnaire. This research was conducted on June 1-20, 2024. The measuring instruments of this study were observation sheets and Spearman analysis. The results of this study indicate that most of the time recovering consciousness 25 minutes in patients after general anesthesia with 2%-2,5% volatile sevoflurane, namely 36 (28.1%) respondents while a small part of the time recovering consciousness 45 minutes with volatile sevoflurane 2%-2.5%, namely 1 (0.8%) respondent. From statistical tests with Spearman analysis with a p value of 0.028 (p < 0.05) with a contingency coefficient of 0.105. It was concluded that there was a relationship between volatile sevoflurane and time to recover consciousness in patients after general anesthesia at Kardinah Hospital, Tegal City.